Religious vocabulary in Aromanian compared to Romanian - Klimkowski, Tomasz (Balcanica Posnaniensia. Acta et studia, 2015)
The first layer of Aromanian Christian terminology is common for all the Balkan Romance languages. It contains a number of inherited Latin terms and some early assimilated Greek loanwords, due to the Oriental origin of Christianity. As for the later layer, the compound of terms related to ecclesiastical organisation and liturgy or to more sophisticated doctrinal concepts, the Balkan Romance languages substantially differ. In Romanian, it was formed on the basis of Slavonic (or Greek via Slavonic), which was used in the Romanian Orthodox Church by the 17th century. The liturgical language of the Aromanians was Greek (maybe except for Moscopole) and therefore, Aromanian mainly based its religious terminology on Greek, but also on Turkish and Albanian, which can be seen in the Aromanian Missal from the second half of the 18th century. In the next centuries, Aromanian religious vocabulary was strongly influenced by Romanian. The contemporary versions of religious texts, including the Bible (e.g. Caciuperi’s translations), introduce a series of Romanian terms instead of the old ones.